Pengaruh Penggunaan Media Pembelajaran Berbentuk Video Microlearning terhadap Peningkatan Kemampuan Qiraah pada Murid MDTA Raudhatul Jannah Nagari Pasia - Fawzan Akbar Sinaga; Supriadi Supriadi; Supratman Zakir; Liza Efriyanti (ANWARUL, 2025)
The limited research on the use of microlearning videos as instructional media for qira’ah (Qur’anic reading) forms the basis of this study, given that students’ low qira’ah proficiency significantly affects the quality of their recitation and comprehension—particularly at MDTA Raudhatul Jannah, Nagari Pasia. This study aims to examine the effect of using microlearning videos on improving students' qira’ah skills. A quantitative approach was employed using a Quasi-Experimental Post-Test Only Design with Nonequivalent Groups. The sample consisted of 40 students selected through cluster random sampling after a population homogeneity test was conducted. Data were collected through a written post-test (20 multiple-choice questions) and an oral qira’ah assessment, then analyzed using an Independent Sample t-test. The results showed that the experimental group had a higher average score of 94.35 compared to the control group’s 81.85, with a significance value (2-tailed) of 0.000 < 0.05. These findings align with microlearning theory, which emphasizes the effectiveness of delivering content in small, focused units, and support previous findings by Park & Kim in different contexts. The study concludes that microlearning videos play a significant role in enhancing students’ qira’ah ability and are suitable for adoption as a learning strategy in basic religious education institutions. The theoretical implications contribute to the literature on integrating microlearning into Qur’anic instruction, while the practical implications recommend the development of educational video content and teacher training for its effective use. The study also opens avenues for further research on broader implementation, considering supporting factors such as parental involvement and student motivation.